The Influence of Amplitude- and Frequency-Dependent Stiffness of Rail Pads on the Random Vibration of a Vehicle-Track Coupled System - Kai Wei; Pan Zhang; Ping Wang; Junhua Xiao; Zhe Luo (Shock and Vibration)
The nonlinear curves between the external static loads of Thermoplastic Polyurethane Elastomer (TPE) rail pads and their compressive deformations were measured. A finite element model (FEM) for a rail-fastener system was produced to determine the nonlinear compressive deformations of TPE rail pads and their nonlinear static stiffness under the static vehicle weight and the preload of rail fastener. Next, the vertical vehicle-track coupled model was employed to investigate the influence of the amplitude- and frequency-dependent stiffness of TPE rail pads on the vehicle-track random vibration. It is found that the static stiffness of TPE rail pads ranges from 19.1 to 37.9 kN/mm, apparently different from the classical secant stiffness of 26.7 kN/mm. Additionally, compared with the nonlinear amplitude- and frequency-dependent stiffness of rail pads, the classical secant stiffness would not only severely underestimate the random vibration acceleration levels of wheel-track coupled system at frequencies of 65–150 Hz but also alter the dominant frequency-distribution of vehicle wheel and steel rail. Considering that these frequencies of 65–150 Hz are the dominant frequencies of ground vibration accelerations caused by low-speed railway, the nonlinear amplitude- and frequency-dependent stiffness of rail pads should be taken into account in prediction of environment vibrations due to low-speed railway.